2000
DOI: 10.1121/1.428428
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of sound transmission loss through multilayered panels by using Gaussian distribution of directional incident energy

Abstract: In this study, a new prediction method is suggested for sound transmission loss (STL) of multilayered panels of infinite extent. Conventional methods such as random or field incidence approach often given significant discrepancies in predicting STL of multilayered panels when compared with the experiments. In this paper, appropriate directional distributions of incident energy to predict the STL of multilayered panels are proposed. In order to find a weighting function to represent the directional distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 21 publications
3
50
0
3
Order By: Relevance
“…This normalized energy density shows a similarity with the results by Kang and co-workers. 14,15 Because the source S2 is far from the target surface, only a few direct rays ͑172 out of 8000͒ strike the surface. It was found that there is an upper limiting angle of direct incidence, 42°for S2 case.…”
Section: A Rectangular Roommentioning
confidence: 99%
“…This normalized energy density shows a similarity with the results by Kang and co-workers. 14,15 Because the source S2 is far from the target surface, only a few direct rays ͑172 out of 8000͒ strike the surface. It was found that there is an upper limiting angle of direct incidence, 42°for S2 case.…”
Section: A Rectangular Roommentioning
confidence: 99%
“…2,14,26,27,[34][35][36] The problem of modeling cavity absorption was already mentioned by Hongisto. 17 The most problematic situation that none of the models investigated by Hongisto can deal with is very thin and empty cavities (d < 30 mm).…”
Section: Cavity Absorptionmentioning
confidence: 99%
“…TMM simulation for infinite structures and diffuse sound field excitation shows a large underestimation of STL in a broad frequency band between the mass-spring-massresonance of the structure around 200 Hz and the coincidence frequencies around 2000 Hz. Even after applying correction terms for the diffraction effects by spatially windowing the results, 28 or a Gaussian distribution of incident energy, 27 the discrepancy remains. The agreement between simulation and measurement result is good over a broad frequency range.…”
Section: Vibro-acoustic Couplingmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Furthermore, better agreement was found using smoothly varying angular distributions of incident energy rather than using a sharp truncation at 78°by Kang and co-workers. 20 Makita and Hidaka 21 discussed possible variations of absorption coefficients in non-uniform energy field. Recently, Jeong 17 investigated incident energy density distributions for a rectangular and an irregular room using a beam tracing technique.…”
Section: ͑1͒mentioning
confidence: 99%